'Candidatus Xiphinematincola pachtaicus' gen. nov., sp. nov., an endosymbiotic bacterium associated with nematode species of the genus Xiphinema (Nematoda, Longidoridae). Issue 7 (21st July 2021) - Palomares-Rius, Juan E.; Gutiérrez-Gutiérrez, Carlos; Mota, Manuel; Bert, Wim; Claeys, Myriam; Yushin, Vladimir V.; Suzina, Natalia E.; Ariskina, Elena V.; Evtushenko, Lyudmila I.; Subbotin, Sergei A.; Castillo, Pablo
Abstract : An intracellular bacterium, strain IAS T, was observed to infect several species of the plant-parasitic nematode genus Xiphinema ( Xiphinema astaregiense, Xiphinema incertum, Xiphinema madeirense, Xiphinema pachtaicum, Xiphinema parapachydermum and Xiphinema vallense ). The bacterium could not be recovered on axenic medium. The 16S rRNA gene sequence of IAS T was found to be new, being related to the family Burkholderiaceae, class Betaproteobacteria. Fungal endosymbionts Mycoavidus cysteinexigens B1-EB T (92.9 % sequence identity) and ' Candidatus Glomeribacter gigasporarum' BEG34 (89.8 % identity) are the closest taxa and form a separate phylogenetic clade inside Burkholderiaceae. Other genes ( atpD, lepA and recA ) also separated this species from its closest relatives using a multilocus sequence analysis approach. These genes were obtained using a partial genome of this bacterium. The localization of the bacterium (via light and fluorescence in situ hybridization microscopy) is in the X. pachtaicum females clustered around the developing oocytes, primarily found embedded inside the epithelial wall cells of the ovaries, from where they are dispersed in the intestine. Transmission electron microscopy (TEM) observations supported the presence of bacteria inside the nematode body, where they occupy ovaries and occur inside the intestinal epithelium. Ultrastructural analysis of the bacterium showed cells that appear as mostly irregular, slightly curved rods with rounded ends, 0.8–1.2 µm wide and 2.5–6.0 µm long, possessing a typical Gram-negative cell wall. The peptidoglycan layer is, however, evident only occasionally and not detectable by TEM in most cells. Another irregularly occurring shell surrounding the endosymbiont cells or the cell clusters was also revealed, probably originating from the host cell membrane. Flagella or spore-like cells do not occur and the nucleoid is diffusely distributed throughout the cell. This endosymbiont is transmitted vertically through nematode generations. These results support the proposal of IAS T as a new species, although its obligate intracellular and obligate endosymbiont nature prevented isolation of a definitive type strain. Strain IAS T is therefore proposed as representing ' Candidatus Xiphinematincola pachtaicus' gen. nov., sp. nov.